Pendidikan jasmani dalam Al-Qur’an: Studi tafsir tematik - Nopel, Perisi (Edu Sportivo: Indonesian Journal of Physical Education, 2022)
The research objectives are (1) to determine physical education in the Koran, (2) to determine the relevance of physical education in the world of Islamic education. The type of research writer who uses descriptive qualitative research is to examine the verses of the Koran about physical education. The data sources of this study used secondary data and primary data. The method of data collection in this study used the thematic interpretation method. While the research data processing techniques using Content Analysis and literature review. The results of this study are (1) physical education in the Koran is; (a) maintain cleanliness (Al-Maidah: 6, An-NISAA: 43, Al-Baqarah: 222), (b) regulate diet (Al-A'raf: 31, Al-Mukmin: 43, Al-Maidah: 5), (c) rest and regular exercise (Al-Furqan: 47, Al-Qashahs: 73, An-Naba': 9, Ar-Rum: 23). (2) The relevance of physical education in education. Physical education is integrated with the goal of Islamic education, namely the development of the potential of students to become human beings who believe and fear God Almighty, noble, healthy, knowledgeable, capable, creative, and become democratic and responsible citizens.